Nordic and Baltic Perspectives in Canadian Studies An Interdisciplinary Approach to Northern Spaces Narratives - Bédard-Goulet, Sara; Premat, Christophe (Stockholm Studies in Romance Languages, 2023)
The challenge of this book is to go beyond the realm of cultural diplomacy when it comes to outlining Canadian studies. Based on renewed research into the imaginary of the North, the book explores transnordic narrative spaces between Canada, the Nordic countries and the Baltic states. Although the book takes cultural studies as its theoretical basis, opposing a diplomatic perspective and arguing that there is a specificity to Canadian culture that requires the attention of the academic world, each chapter draws on theories and methods specific to the various fields of the humanities and social sciences concerned with addressing the narratives (understood in a broad sense and including visual narratives) of this northern space.